Introduction: Pursuing excellence in social security administration: Social security's technical and administrative improvement: Pursuing excellence. (July 2016) - McKinnon, Roddy
Abstract: This 2016 special issue addresses the topic of excellence in social security administration. For the International Social Security Association, "excellence" is most usually associated with ensuring that the technical processes and administrative procedures that underpin the delivery of social security benefits and services are high‐performing, well‐governed and sustainable. But it also refers to the covered population's perceptions of the quality and adequacy of the services and benefits provided. The academic literature on "social security" is immense, but the larger part of this published research addresses questions of social security theory and policy. The critical, analytical literature on social security administration, including that which marries theoretical analysis with the empirical evidence of administrative performance, is thus smaller. A major aim of this special issue is to make a contribution to redressing this imbalance. This is done not only to support and stimulate research that draws equally on empirical evidence and the theoretical literature, but in a very practical sense to better take into account and provide responses to the increasingly complex operational challenges facing social security administrations